Optimization of hard clams, polychaetes, physical disturbance and denitrifying bacteria of removing nutrients in marine sediment. Issue 1 (15th September 2016) - Shen, Hui; Thrush, Simon F.; Wan, Xihe; Li, Hui; Qiao, Yi; Jiang, Ge; Sun, Ruijian; Wang, LiBao; He, Peimin
Abstract: Marine organisms are known to play important roles in transforming nutrients in sediments, however, guidelines to optimize sediment restoration are not available. We conducted a laboratory mesocosm experiment to investigate the role of hard clams, polychaetes, the degree of physical disturbance and denitrifying bacterial concentrations in removing total nitrogen (TN), total phosphorus (TP), and total organic carbon (TOC) in marine sediments. Response surface methodology was employed to analyze the results of initial experiments and in a subsequent experiment identified optimal combinations of parameters. Balancing the TN, TP, TOC removal efficiency, our model predicted 39% TN removal, 33% TP removal, and 42% TOC removal for a 14-day laboratory bioremediation trial using hard clams biomass of 1.2 kg m − 2, physical disturbance depth of 16.4 cm, bacterial density of 0.18 L m − 2, and polychaetes biomass of 0.16 kg m − 2, respectively. These results emphasize the value of combining different species in field-based bioremediation.